2019
DOI: 10.18632/aging.101804
|View full text |Cite
|
Sign up to set email alerts
|

Shaoyao Gancao Tang (SG-Tang), a formulated Chinese medicine, reduces aggregation and exerts neuroprotection in spinocerebellar ataxia type 17 (SCA17) cell and mouse models

Abstract: Spinocerebellar ataxia (SCA) type 17 is an autosomal dominant ataxia caused by expanded polyglutamine (polyQ) tract in the TATA-box binding protein (TBP). Substantial studies have shown involvement of compromised mitochondria biogenesis regulator peroxisome proliferator-activated receptor gamma-coactivator 1 alpha (PGC-1α), nuclear factor erythroid 2-related factor 2 (NRF2), nuclear factor-Y subunit A (NFYA), and their downstream target genes in the pathogenesis of polyQ-expansion diseases. The extracts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 70 publications
5
22
0
Order By: Relevance
“…Interestingly, a FDA approved drug called piperine is found to induce MANF activity and to improve motor performance of SCA17 knockin mice (Guo et al, 2018). Similarly, treatment with Shaoyao Gancao Tang reduces mTBP aggregation, increases expression of NFYA and HSPA5 as well as PGC-1α and NRF2, and improves motor phenotypes of SCA17 transgenic mice (Chen et al, 2019).…”
Section: Sca17mentioning
confidence: 99%
“…Interestingly, a FDA approved drug called piperine is found to induce MANF activity and to improve motor performance of SCA17 knockin mice (Guo et al, 2018). Similarly, treatment with Shaoyao Gancao Tang reduces mTBP aggregation, increases expression of NFYA and HSPA5 as well as PGC-1α and NRF2, and improves motor phenotypes of SCA17 transgenic mice (Chen et al, 2019).…”
Section: Sca17mentioning
confidence: 99%
“…Shaoyao Gancao Tang is a Chinese traditional herbal formulation consisting of Paeonia lactiflora and Glycyrrhiza uralensis in a 1:1 ratio. In a study by Chen et al [ 65 ], the antioxidant activities of the formulation were evaluated in in vitro models of SCA17 using HEK 293 and SH-SY5Y cells expressing mutant TATA-box binding protein (TBP), and in vivo transgenic mouse model of SCA17 overexpressing TBP. Pre-treatment with the formulation (0.001–100 µg/mL) in cells for 8 h demonstrated no cytotoxicity, as indicated by MTT assay.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, suppression of polyQ aggregation was observed in cells, as shown by low GFP intensity. Administration of 0.4% Shaoyao Gancao Tang in the drinking water of the mouse model improved gait coordination and suppressed hyperactivity, as indicated by footprint and locomotor test, respectively [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…NRF2 activation can mitigate a number of neurodegenerative diseases including HD [28]. We and other researchers have shown that NRF2 expression is impaired in SCA3 and SCA17 models, and agents enhancing NRF2 rescue the phenotypes induced by mutant polyQ [2,22,[29][30][31][32]. Taken together, we planned to examine more compounds that may activate NRF2 in our SCA17 cell models.…”
Section: Introductionmentioning
confidence: 94%
“…The authors further showed that increased ROS and the activated AMPK-α1 act in a vicious cycle contributing to the mHTT-induced neuronal death in the striatum of HD mice [41]. Since previously our SCA17 models displayed increased oxidative stress [29,32,42], we planned to investigate the role of AMPK in the pathogenesis of SCA17 and if aggregation-inhibitory compounds act on the AMPK pathway.…”
Section: Introductionmentioning
confidence: 99%